2018
DOI: 10.1101/443531
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microglial SIRPα regulates the emergence of CD11c+ microglia and demyelination damage in white matter

Abstract: 28A characteristic subset of microglia expressing CD11c appears in response to brain 29 damage. However, the functional role of CD11c + microglia, as well as the mechanism of 30 its induction, are poorly understood. Here we report that the genetic ablation of signal 31 regulatory protein α (SIRPα), a membrane protein, induced CD11c + microglia in the 32 brain white matter. Mice lacking CD47, a physiological ligand of SIRPα, and 33 microglia-specific SIRPα knockout mice exhibited the same phenotype, suggesting … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…Notably, some microglial subset can be induced by neighboring microglia. When signal regulatory protein α (SIRPα), a membrane protein, was genetically ablated, the number of CD11c + microglia was significantly increased in white matter of the brain . Microglia‐specific ablation of SIRPα alleviated cuprizone‐induced demyelination, suggesting that microglial SIRPα suppresses the induction of CD11c + microglia and demyelination damage in white matter, possibly involving indirect roles on oligodendrocyte lineage cells.…”
Section: Microglia‐derived Factors and Oligodendrocytes Lineage Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, some microglial subset can be induced by neighboring microglia. When signal regulatory protein α (SIRPα), a membrane protein, was genetically ablated, the number of CD11c + microglia was significantly increased in white matter of the brain . Microglia‐specific ablation of SIRPα alleviated cuprizone‐induced demyelination, suggesting that microglial SIRPα suppresses the induction of CD11c + microglia and demyelination damage in white matter, possibly involving indirect roles on oligodendrocyte lineage cells.…”
Section: Microglia‐derived Factors and Oligodendrocytes Lineage Cellsmentioning
confidence: 99%
“…When signal regulatory protein α (SIRPα), a membrane protein, was genetically ablated, the number of CD11c + microglia was significantly increased in white matter of the brain. 96 Altogether, depending on the pathological stage of white matter damage, different subsets of microglia could affect the fate of OPCs and oligodendrocytes by secreting factors of various effects (Figure 1).…”
Section: Crog Lia-derived Fac Tor S and Oli G Odendro C Y Te S Lmentioning
confidence: 99%
“…We recently showed that the ablation of SIRPα specifically in microglia resulted in spontaneous activation of these cells in the CNS and protection from demyelination damage [37]. However, we found that CD11c expression was not upregulated in microglia of Sirpa ΔDC mice (data not shown), indicating that SIRPα is not ablated in microglia of these mice.…”
Section: Discussionmentioning
confidence: 61%
“…Interestingly, this subset of microglia is necessary for primary myelination and is involved in protection from EAE 16‐18 . CD11c+ microglia can be induced by CSF1R stimulation, 16 as well as by blocking Sirpα‐CD47 signalling 19 . CSF1R stimulation led to EAE suppression 16 …”
Section: Cns‐resident Myeloid Cells In Inflammatory Demyelinating Dismentioning
confidence: 99%